Sources of Competitive Advantage Measurement in the Minor Export Crop Sector in Sri Lanka: Result from Pilot Study - Sachitra, K.M.V.; Chong, Siong- Choy; Khin, A.A. (Sciencedomain International, 2016)
Purpose: This study aims to identify the items associated with sources of competitive advantage in the minor export crop sector. Design/Methodology/Approach: The measures were identified based on literature review and expert opinions which took into account theories of resource-based view (RBV) and firm-specific dynamic capabilities. They were piloted on 30 farmers engaged in the commercial cultivation of minor export crops of cinnamon, cloves and pepper in Sri Lanka. The measures were subject to reliability and validity tests to ascertain the items to be retained to represent the sources of competitive advantage in the minor export crop sector. Findings: The RBV comprises human asset (7 items), financial asset (7 items), physical asset (6 items) and reputation (5 items), whilst firm-specific dynamic capabilities consist of quality management capability (8 items) and marketing capability (8 items). About 19 items were identified as measures of competitive advantage. The statistical results showed that 5 items were retained for each of the human and financial assets, respectively; 5 and 4 items were retained for physical assets and reputation; 5 items were retained for each of the quality management capability and marketing capability, respectively; and 12 items were retained as measures of competitive advantage in the minor export crop sector. Originality/Value: Although the results exemplify the initial step towards a more detailed research in the future, they shed light in terms of the future development of a simple specification model, as well as a diamond specification model specifically for the sector. Several implications are provided with the intention of advancing research in this important yet interesting area.
Keywords: Agribusiness sector; competitive advantage; dynamic capabilities; reliability; resourcebased view; validity